Assessment of Legibility of Handwritten Prescriptions and Adherence to W.H.O. Prescription Writing Guidelines in Ahmadu Bello University Teaching Hospital Zaria - Kaduna State, Nigeria - Abba Khalid Abdullahi; Ibrahim Seneire Fatima; Umar Abdurrahman; Salihu Isa Sa'adatu; Abubakar Bukhari Hafsat; Haruna Abdullahi Abdulrasheed; Umar Abubakar; Igashi Dorcas; Sanni Hameed Kehinde; Adam Ibrahim Bashir; Muhammad Kabir Musa (University of Minnesota Libraries Publishing, 2023)
Introduction: The issues of incorrectness and incompleteness for written prescriptions may result to dispensing errors and unintended outcomes of care. The objective of the study was to assess the legibility of handwritten prescriptions and adherence to W.H.O. prescription writing guidelines in Ahmadu Bello University Teaching Hospital Zaria. Method: A cross-sectional prospective study design was used, and existing prescriptions were sampled from selected in-patient and outpatient pharmacy units of Ahmadu Bello University Teaching Hospital Zaria. This was approved by the ethics and research committee of the institution. The prescriptions were then evaluated for quality based on the layout, legibility, and clarity of the details in the prescriptions and screened for medication errors. Result: The extent of prescribing drugs by generic name was (68.37%), the legibility percentage was moderate and the percentage of prescriptions in which details of the drug, route of administration, and duration of treatment were complete was 85.23%, 80.80%, and 82.40%, respectively. The doctor's signature (84.87%) was present in the prescriptions. Many of the prescribers did not use to indicate patients' weight, age, and clinic on prescriptions, these are deviations from good prescribing practices while total medication error was 38.01%. Conclusion: Prescribers have a duty of care to their patient and a professional duty to their colleagues (pharmacists) to ensure drug prescriptions are readily identifiable. Interventional techniques such as the use of printed or electronic prescriptions can improve the ease of interpreting information and reduce medication errors.